METHODS OF PERCUTANEOUSFIXATION OF FRAGMENTS IN SUPRACONDYLAR HUMERUS FRACTURES IN CHILDREN AND ADOLESCENTS - Buryanov, Olexander; Kvasha, Volodymyr; Naumenko, Valerija; Kovalchuk, Dmytro; Pylypchuk, Oleg; Omelchenko, Taras; Rohozynskyi, Valentyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
The aim of this study is to conduct a meta-analysis and evaluate the clinical efficacy and safety of crossed and lateral fixation of fragments in supracondylar humerus fractures in children and adolescents. Methods. A comprehensive literature search was conducted in the PubMed and EMBASE databases from 2015 to December 2023 using the following search terms: "supracondylar fractures of distal humerus in pediatric patients", "treatment", "methods of fixation", "pinning configuration", "biomechanical analysis of pin placement". According to the inclusion and exclusion criteria, the literature sources of anatomic-biomechanical and clinical studies related to the use of crossed and lateral fixation of fragments in the case of supracondylar fractures of the humerus in children and adolescents were selected and analyzed. The review was prepared in accordance with the recommendations of the "Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines." Results. A comparison of results from experimental studies investigating the degree of stabilization achieved in the crossed and lateral configurations of fixation structures reveals conflicting conclusions due to the heterogeneity of designs implemented. The principal limitation of lateral fixation is the increased risk of failure of fixation. The outcomes of clinical trials (Flynn criteria) demonstrate that both types of fracture fixation yield equivalent clinical outcomes. One disadvantage of crossed fixation is the risk of iatrogenic ulnar nerve damage, while another disadvantage is the increased complexity of the surgical technique. Conclusions. The results of anatomical and biomechanical studies indicate that cross-fixation provides more rigid fixation of fragments in supracondylar humerus fractures in children and adolescents. Nevertheless, clinical outcomes based on radiological and functional data (including Flynn’s score) demonstrate no significant distinction between the two types of fixation configurations. However, they do indicate a notable risk of iatrogenic ulnar nerve damage in cross fixation, which justifies the necessity to utilise a mini-open technique in the medial fixation construct.